Myocarditis-like Episodes in Patients with Arrhythmogenic Cardiomyopathy: A Systematic Review on the So-Called Hot-Phase of the Disease - Riccardo Bariani; Ilaria Rigato; Alberto Cipriani; Maria Bueno Marinas; Rudy Celeghin; Cristina Basso; Domenico Corrado; Kalliopi Pilichou; Barbara Bauce (Biomolecules, 2022)
Arrhythmogenic cardiomyopathy (ACM) is a genetically determined myocardial disease, characterized by myocytes necrosis with fibrofatty substitution and ventricular arrhythmias that can even lead to sudden cardiac death. The presence of inflammatory cell infiltrates in endomyocardial biopsies or in autoptic specimens of ACM patients has been reported, suggesting a possible role of inflammation in the pathophysiology of the disease. Furthermore, chest pain episodes accompanied by electrocardiographic changes and troponin release have been observed and defined as the “hot-phase” phenomenon. The aim of this critical systematic review was to assess the clinical features of ACM patients presenting with “hot-phase” episodes. According to PRISMA guidelines, a search was run in the PubMed, Scopus and Web of Science electronic databases using the following keywords: “arrhythmogenic cardiomyopathy”; “myocarditis” or “arrhythmogenic cardiomyopathy”; “troponin” or “arrhythmogenic cardiomyopathy”; and “hot-phase”. A total of 1433 titles were retrieved, of which 65 studies were potentially relevant to the topic. Through the application of inclusion and exclusion criteria, 9 papers reporting 103 ACM patients who had experienced hot-phase episodes were selected for this review. Age at time of episodes was available in 76% of cases, with the mean age reported being 26 years ± 14 years (min 2–max 71 years). Overall, 86% of patients showed left ventricular epicardial LGE. At the time of hot-phase episodes, 49% received a diagnosis of ACM (Arrhythmogenic left ventricular cardiomyopathy in the majority of cases), 19% of dilated cardiomyopathy and 26% of acute myocarditis. At the genetic study, Desmoplakin (DSP) was the more represented disease-gene (69%), followed by Plakophillin-2 (9%) and Desmoglein-2 (6%). In conclusion, ACM patients showing hot-phase episodes are usually young, and DSP is the most common disease gene, accounting for 69% of cases. Currently, the role of “hot-phase” episodes in disease progression and arrhythmic risk stratification remains to be clarified.